Pre-weaning and post-weaning growth and its relationship to feedlot performance and carcass characteristics of bull calves - El-Shafia, S.A.; Osman, A.H.; Khalil, K.A.; Tawfik, E.S. (1976)
Growth potential of Sudanese indigenous cattle was investigated. Performances on grass and concentrate feeding were evaluated. Data on various levels of feeding and growth, the interrelationship between body weight gains and carcass traits included.